2019
DOI: 10.3389/fpls.2019.00978
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Conditions and Molecular Determinants Involved in Agrobacterium Lifestyle in Tumors

Abstract: The study of pathogenic agents in their natural niches allows for a better understanding of disease persistence and dissemination. Bacteria belonging to the Agrobacterium genus are soil-borne and can colonize the rhizosphere. These bacteria are also well known as phytopathogens as they can cause tumors (crown gall disease) by transferring a DNA region (T-DNA) into a wide range of plants. Most reviews on Agrobacterium are focused on virulence determinants, T-DNA int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 153 publications
(259 reference statements)
0
12
0
1
Order By: Relevance
“…A physiologically active crown gall produces specific nutrients (opines) utilizable by microorganisms, providing a rich niche for plant-associated bacteria to colonize, grow, and form complex ecological interactions ( 34 37 ). The microbial communities involved in opine ecology are not limited to Agrobacterium members.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A physiologically active crown gall produces specific nutrients (opines) utilizable by microorganisms, providing a rich niche for plant-associated bacteria to colonize, grow, and form complex ecological interactions ( 34 37 ). The microbial communities involved in opine ecology are not limited to Agrobacterium members.…”
Section: Discussionmentioning
confidence: 99%
“…The genome of Pseudomonas kilonensis strain 1855-344, which can catabolize octopine, was recently shown to contain an octopine-catabolic operon named ooxAB ( 40 ). Successful colonization and long-term persistence of Agrobacterium strains on/in crown gall tissue depend partly on competition for opine nutritive resources, either between the agrobacteria or among other microorganisms, such as pseudomonads, Sinorhizobium spp., coryneform bacteria, or even fungal species such as Cylindrocarpon heteronema and Fusarium solani ( 36 , 37 ). It was recently shown that the microbial community of natural grapevine ( Vitis vinifera ) crown galls caused by Allorhizobium vitis contains more than 150 bacterial species, among which members of Pseudomonas , Sphingomonas , and Erwinia were more common ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptomic and/or phenotypic characterizations of the rirA mutant have demonstrated RirA as an iron-responsive regulator under free-living conditions in R. leguminosarum ( 26 , 32 ), Sinorhizobium meliloti ( 33 35 ), Sinorhizobium fredii ( 36 ), and Agrobacterium tumefaciens ( 25 , 37 ). RirA is required for pathogenesis of A. tumefaciens on tobacco leaves ( 37 , 38 ). Symbiotic defects were not observed for the rirA mutants of R. leguminosarum ( 26 ) and S. meliloti ( 33 ), both of which undergo irreversible terminal differentiation (impaired reproductive ability) in nodule cells of pea and alfalfa, respectively ( 39 , 40 ).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic transformation by A. tumefaciens is related to its pathogenicity and involves a shift from free‐living to plant‐associated forms. Soilborne A. tumefaciens is widely found in natural habitats, such as the bulk soil and rhizosphere (Meyer et al, 2019), where it is subjected to nutrient limitation and external stress, including pollutants. On sensing phenols and other nutrients secreted from plant wounds, A. tumefaciens moves to wound sites and mediates crown gall formation to create a better environment for survival.…”
Section: Introductionmentioning
confidence: 99%